Alt a 1 Promotes Allergic Asthma In Vivo Through TLR4-Alveolar Macrophages - Hernandez-Ramirez, Guadalupe; Pazos-Castro, Diego; Gonzalez-Klein, Zulema; Resuela-Gonzalez, Jose Luis; Fernandez-Bravo, Sergio; Palacio-Garcia, Lucia; Esteban, Vanesa; Garrido-Arandia, Maria; Tome-Amat, Jaime; Diaz-Perales, Araceli (Frontiers in Immunology, 2022)
The mold Alternaria alternata is one of the main sources of asthma exacerbation, being its major allergen, Alt a 1, indispensable for its development. The main objective of this work was to answer two main questions: 1) can Alt a 1 by itself (without any other context) induce an asthmatic profile in vivo?; and 2) Which molecular mechanisms take place during this phenomenon? To answer both questions, we have developed a mouse model of allergic asthma using only Alt a 1 for mice sensitization. We also made use of in-vitro cellular models and computational studies to support some aspects of our hypothesis. Our results showed that Alt a 1 can induce an asthmatic phenotype, promoting tissue remodeling and infiltration of CD45+ cells, especially eosinophils and macrophages (Siglec F+ and F4/80+). Also, we have found that Alt a 1 sensitization is mediated by the TLR4-macrophage axis.